PENGARUH COUNTRY OF ORIGIN DAN ELECTRONIC-WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN JASA GOFOOD DI KOTA PALEMBANG - Valentina, Felicia; Tyra, M.J; Lina, Lina (Jurnal Keuangan dan Bisnis, 2024)
This research was conducted with the aim of analyzing and knowing the influence of Country Of Origin and Electronic-Word Of Mouth on the purchase decision of GoFood services in Palembang city. The selected population is people who use GoFood services in Palembang city. The sample used in this study was 100 respondents. The sampling technique uses a non-probability sampling technique with purposive sampling method. The data used in this study are primary and secondary data. Primary data is obtained from questionnaires while secondary data uses journals, news, and books. The data analysis techniques used are validity test, reability test, classical assumption test, namely normality test, multicollinearity test, and heteroskedasticity test, multiple linear regression analysis, hypothesis test consisting of t test and coefficient of determination. The results of the study proved that the Country Of Origin has a positive but not significant effect on purchasing decisions. Electronic-Word Of Mouth has a positive and significant effect on purchasing decisions.